Study on Certain Postural Correlations in Oral Rehabilitation - O. Szasz; S. Popsor; Lia Maria Coman; Liana Claudia Soaita (Romanian Society of Oral Rehabilitation, 2010)
Introduction. There is an obvious relationship between general body posture, cranial posture and the masticatory system.The aim of our study was to establish correlations between certain postural parameters wich may be involved in the oral rehabilitation. Material and method. Sixteen subjects, 13 women and 3 men with average age 24.3 asked for informed consent were investigated.The cranio-vertebral angle , the postural balance, the angle between interpupilar line and the plan of occlusion , the angle of head inclination ( EAR-EYE angle) were calculated and the Beighton rheumatological test was also applied. The statistical interpretation of the data was performed using the NCSS / Pass Dawson Edition to calculate the correlation coefficient , coefficient of determination and regression analysis, in order to assess the relationships between postural imbalance and the postural parameters . Results. The regression analysis and the coefficients of correlation showed no correlations or only a weak negative correlation (r = - 0.5416) between average postural imbalance and the postural parameters. Conclusions: (a) the detection of head position is important for the dentist as it involves changes in orthostatic position of mandible,with direct influence on the prosthetic rehabilitation; (b) alth ough the investigated group was numerically small, preliminary results of our study are in concordance with the literature on values determined for the investigated parameters; (c) In our study, only the relationship between postural imbalance and IP-PO angle proved a medium negative correlation (r = -0.54).